1990
DOI: 10.1111/j.1365-2125.1990.tb03655.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and urine aluminium concentrations in healthy subjects after administration of sucralfate [see comments]

Abstract: 1. Sucralfate (basic sucrose aluminium sulphate), a topical intestinal agent, was administered in suspension or granule form to 25 healthy subjects at a total dose of 4 g day‐1 for 21 days. Aluminium in plasma and 24 h urine samples was assayed before, during and after administration of sucralfate by inductively coupled plasma optical emission spectrometry. 2. Sucralfate produced significant increases in plasma and urine aluminium concentrations. On average, plasma aluminium increased from about 2 micrograms 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 14 publications
(17 reference statements)
2
4
1
Order By: Relevance
“…The 24 h excretion of Al that we observed is in agreement with literature values (Allain et al, 1990). The 24 h urinary excretion of Pb (9.8 ,ug 24 h-1) was similar to the value of Behringer etal.…”
Section: Discussionsupporting
confidence: 92%
“…The 24 h excretion of Al that we observed is in agreement with literature values (Allain et al, 1990). The 24 h urinary excretion of Pb (9.8 ,ug 24 h-1) was similar to the value of Behringer etal.…”
Section: Discussionsupporting
confidence: 92%
“…These results contrast with findings for other compounds such as Al hydroxide (3), sucralfate in healthy subjects (23,24), or in patients with peptic ulcer disease with normal renal function (21). Kaehny et al (3) clearly demonstrated high plasma Al levels in normal adults who ingested Al hydroxide, as compared with those receiving Al phosphate and controls.…”
Section: Discussion contrasting
confidence: 83%
“…The article by Allain et al (1990) describing aluminium absorption from sucralfate in subjects with normal renal function complements a report of a similar study in patients with renal insufficiency (Burgess & Muruve, 1991a). Both studies used a 3 week therapeutic course of sucralfate (4 g day-1) and showed increases in serum aluminium concentrations after 1 day with a plateau after 7 days of therapy.…”
Section: Aluminium Absorption Following Sucralfate Therapysupporting
confidence: 66%